1998
DOI: 10.1046/j.1365-2664.1998.3540562.x
|View full text |Cite
|
Sign up to set email alerts
|

Breeding bird communities in pine plantations of the Spanish plateaux: biogeography, landscape and vegetation effects

Abstract: Summary Afforestation with pines (Pinus pinaster and, to a lesser extent, P. pinea and P. halepensis) seems to be the most probable land‐use change over large areas of dry cereal croplands in central Spain in the next 10–20 years. This will be encouraged by changes in the subsidy policies of the Common Agricultural Policy that aim to decrease food production and restore the environmental diversity previously lost through agricultural intensification. This study addresses the factors influencing the richness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
81
2
13

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(105 citation statements)
references
References 28 publications
9
81
2
13
Order By: Relevance
“…Stand size and connectivity to surrounding forest stands are known to be important determinants of forest bird assemblages in both native forests and plantations (e.g. van Dorp and Opdam, 1987;Enoksson et al, 1995;Díaz et al, 1998), implying that smaller isolated patches of forests may have a lower species richness than larger patches of the same habitat. In a Spanish study, Santos et al, (2002) found that native stands of holm oak (Q. ilex) had to be of significantly larger size than similar stands located in central Europe in order to support equal numbers of bird territories and species.…”
Section: Discussionmentioning
confidence: 99%
“…Stand size and connectivity to surrounding forest stands are known to be important determinants of forest bird assemblages in both native forests and plantations (e.g. van Dorp and Opdam, 1987;Enoksson et al, 1995;Díaz et al, 1998), implying that smaller isolated patches of forests may have a lower species richness than larger patches of the same habitat. In a Spanish study, Santos et al, (2002) found that native stands of holm oak (Q. ilex) had to be of significantly larger size than similar stands located in central Europe in order to support equal numbers of bird territories and species.…”
Section: Discussionmentioning
confidence: 99%
“…The landscape matrix should include a high percentage of poplar plantations, with a distance between the plantations of less than 400 m, to provide forest bird species with well connected supplementary forest habitats. However, as the effect of large scale forest plantations in agricultural areas may also adversely affect threatened bird communities of open habitats (Diaz et al 1998;Reino et al 2009), we suggest that future poplar plantations might be considered within a global landscape planning perspective taking into account all relevant bird habitats such as grasslands and riparian forests.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the effect on bird diversity of increasing area of planted forests has already been tested in Mediterranean landscapes (see Diaz et al 1998;Reino et al 2009), it has seldom been tested in landscapes including remnants of riparian forest, poplar plantations and agricultural land.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in many European countries, some parts of open habitats, especially less productive ones, have been afforested within the framework of programs to increase forest cover. This has had an additional negative impact on many farmland birds (Diaz et al 1998;Marchesi & Sergio 2005). The transformations of farmland habitat resulted in the decline of many bird species inhabiting the open landscape in Central and Eastern Europe (Donald et al 2006;Chylarecki & Jawińska 2007;Lawicki et al 2011).…”
Section: Introductionmentioning
confidence: 99%